Environment-friendly modified nylon material and preparation method thereof

By adding modified lignocellulose and nanoboronitride with graphene quantum dots to the nylon material and using specific modifiers, the problem of insufficient heat resistance in high temperature environments is solved, and the uniformity and environmental protection of material properties are achieved.

CN119592061APending Publication Date: 2025-03-11WUXI CHANGAN POLYMER MATERIAL FACTORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411465240.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing nylon materials have poor heat resistance in high temperature environments, and traditional modification methods may lead to uneven material properties and affect environmental protection.

Method used

The heat resistance and environmental protection of nylon materials are improved by adding modified lignocellulose and nanoboronitride supported by graphene quantum dots, and modifiers such as tetrabutyl titanate, tributyl citrate and silane coupling agent during the preparation process.

Benefits of technology

It significantly improves the heat resistance, toughness and strength of nylon materials, ensures the reliability and stability of the material under high temperature environments, and enhances the environmental protection of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592061A_ABST
    Figure CN119592061A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer nylon materials, in particular to an environment-friendly modified nylon material and a preparation method thereof, and aims to solve the problem of poor heat resistance of nylon materials in related technologies. The preparation method of the environment-friendly modified nylon material comprises the following steps: S1, adding equal amounts of oxalic acid and 1, 6-hexamethylenediamine into a reaction kettle, heating to 180-200 DEG C, uniformly stirring, adding tetrabutyl titanate, heating to 250 DEG C under the protection of nitrogen, and reacting for 3-4 hours to obtain a nylon head product; s2, providing a nylon head product, adding modified lignocellulose and nano boron nitride loaded with graphene quantum dots into the nylon head product, preheating at 70 DEG C for 1 hour, and uniformly mixing in a high-speed mixer to obtain a mixed material; and S3, adding the mixed material into a twin-screw extruder, adding zinc phytate, an antioxidant and a compatilizer at the same time, carrying out extrusion granulation, and in the extrusion process, adding a 30wt% triethanolamine solution according to 1.5% of the total mass of the mixed material to obtain the environment-friendly modified nylon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer nylon materials, and in particular to an environmentally friendly modified nylon material and a preparation method thereof. Background Art

[0002] Nylon is a widely used engineering plastic, and its main preparation process includes polymerization, processing and post-processing. Although nylon has a certain degree of heat resistance, it is still insufficient in some high-temperature applications, such as automobile engine peripheral parts, electrical systems and other parts, which require the use of nylon materials with high heat resistance to ensure reliability and stability in high temperature environments. Electronic or electrical equipment will generate heat during operation, requiring nylon materials to be used for a long time at high temperatures. At the same time, in these fields, nylon materials are usually required to have environmentally friendly properties to avoid nylon materials from releasing harmful gases in high temperature environments.

[0003] Related technologies usually include chemical modification of nylon molecules, such as grafting, cross-linking, etc., or the addition of glass fibers or carbon fibers to enhance the toughness and heat resistance of nylon materials. However, the chemical reagents used in chemical modification may cause environmental pollution, and the dispersion of glass fibers or carbon fibers in the nylon matrix is ​​difficult to ensure. If the dispersion is uneven, it will cause local stress concentration and reduce the performance of the material. Summary of the invention

[0004] The present application provides an environmentally friendly modified nylon material and a preparation method thereof, so as to solve the problem of poor heat resistance of nylon material in the related art.

[0005] In a first aspect, a method for preparing an environmentally friendly modified nylon material is provided, which comprises the following steps:

[0006] S1. Add equal amounts of oxalic acid and 1,6-hexanediamine into a reaction kettle, heat to 180-200° C., stir evenly, add tetrabutyl titanate, heat to 250° C. under nitrogen protection, react for 3-4 hours, and obtain a primary nylon product, wherein the amount of tetrabutyl titanate added is 0.5-1.5% of the total mass of oxalic acid and 1,6-hexanediamine;

[0007] S2, providing 70 to 80 parts of the nylon primary product, adding 10 to 15 parts of modified wood cellulose and 8 to 12 parts of nano-boron nitride loaded with graphene quantum dots to the nylon primary product, preheating at 70° C. for 1 hour, and mixing in a high-speed mixer at a speed of 1500 to 2000 r / min to obtain a mixed material;

[0008] The preparation of the modified lignocellulose comprises the following steps:

[0009] The lignocellulose and the modifier solution are mixed in a mass ratio of 3:1 to 4:1, and stirred at 70 to 80° C. for 2 to 4 hours to obtain modified lignocellulose, wherein the modifier solution includes tributyl citrate and one of tetrabutyl titanate and silane coupling agent KH-550;

[0010] S3. Add the mixture into a twin-screw extruder, add zinc phytate, an antioxidant and a compatibilizer at the same time, perform extrusion granulation, and during the extrusion process, add 30wt% triethanolamine solution according to 1.5% of the total mass of the mixture to obtain an environmentally friendly modified nylon material, wherein the zinc phytate accounts for 5-10% of the mass of the mixture, the antioxidant accounts for 2-5% of the mixture, and the compatibilizer accounts for 3-8% of the mixture, the antioxidant is selected from one of natural vitamin C and tea polyphenols, and the compatibilizer is selected from tributyl citrate grafted polyethylene.

[0011] Preferably, the preparation of the nano boron nitride loaded with graphene quantum dots comprises the following steps:

[0012] Nano boron nitride and graphene quantum dots were mixed in a mass ratio of 10:3, added into deionized water in a mass ratio of 1:4, and ultrasonically treated at 40-50° C. for 3-4 hours to obtain nano boron nitride loaded with graphene quantum dots.

[0013] Preferably, the S2 further includes:

[0014] Add 8-12 parts of chitosan grafted polylactic acid modified with nano-hydroxyapatite:

[0015] Chitosan grafted polylactic acid and nano-hydroxyapatite are mixed in a mass ratio of 5:2, and then added into an acetic acid solution in a mass ratio of 1:3, and reacted with stirring at 60-70°C for 3-4h to obtain nano-hydroxyapatite modified chitosan grafted polylactic acid.

[0016] Preferably, the preparation of chitosan grafted polylactic acid comprises the following steps:

[0017] Chitosan and 2 wt % acetic acid solution were mixed in a mass ratio of 1:10, and stirred at 25° C. until the chitosan was completely dissolved to obtain a chitosan solution;

[0018] Polylactic acid and dichloromethane are mixed in a ratio of 1:5, and stirred at 40°C until the polylactic acid is completely dissolved to obtain a polylactic acid solution, and the polylactic acid solution is added dropwise to the chitosan solution, and ammonium persulfate accounting for 2% of the total mass of the chitosan solution and the polylactic acid solution is added, and stirred at 50°C for 5 hours to obtain a chitosan grafted polylactic acid crude product solution;

[0019] The crude chitosan grafted polylactic acid product solution was allowed to stand for 2 hours and then filtered to obtain a solid, which was washed and dried to obtain chitosan grafted polylactic acid.

[0020] Preferably, the modifier solution comprises tributyl citrate and silane coupling agent KH-550, the volume ratio of the tributyl citrate to the silane coupling agent KH-550 is 3:2, and the concentration of the triethyl citrate is 50wt%.

[0021] Preferably, the modifier solution comprises triethyl citrate and tetrabutyl titanate, the mass ratio of triethyl citrate to tetrabutyl titanate is 2:1, and the concentration of triethyl citrate is 50wt%.

[0022] In a second aspect, an environmentally friendly modified nylon material is provided, which is manufactured by any of the environmentally friendly modified nylon material preparation methods described above.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present application provides an environmentally friendly modified nylon material and a preparation method thereof. By adding modified lignocellulose, the dispersibility of lignocellulose in nylon is improved, which helps to enhance the strength and toughness of the nylon material. At the same time, due to the tighter combination with nylon, it helps to improve the heat resistance. The tributyl citrate in the modifier has good biocompatibility and plasticizing effect, which can improve the flexibility of lignocellulose and help the dispersion and compatibility of lignocellulose in nylon.

[0025] Nano boron nitride has a high specific surface area and active sites, and can form physical adsorption and chemical bonds with nylon molecules. The flaky structure of nano boron nitride can hinder the transfer of heat and improve the heat resistance of nylon. Its high thermal conductivity can quickly disperse heat, reduce local overheating, and improve the thermal stability of nylon materials. Graphene quantum dots with excellent thermal conductivity and mechanical properties are loaded onto nano boron nitride to further improve the performance of nano boron nitride, thereby enhancing the heat resistance, toughness and strength of nylon materials. Therefore, it can solve the problem of poor heat resistance of nylon materials in related technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 The present invention provides a flow chart of the method for preparing the environmentally friendly modified nylon material. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] See also Figure 1 The present invention provides a method for preparing an environmentally friendly modified nylon material, which can solve the problem of poor heat resistance of nylon materials in the related art. The method for preparing the environmentally friendly modified nylon material comprises the following steps:

[0030] S1. Add equal amounts of oxalic acid and 1,6-hexanediamine into a reaction kettle, heat to 180-200° C., stir evenly, add tetrabutyl titanate, heat to 250° C. under nitrogen protection, react for 3-4 hours, and obtain a primary nylon product, wherein the amount of tetrabutyl titanate added is 0.5-1.5% of the total mass of oxalic acid and 1,6-hexanediamine;

[0031] Tetrabutyl titanate helps to promote the polycondensation reaction of adipic acid and 1,6-hexanediamine, increase the reaction rate and the molecular weight of the product, and further improve the strength and heat resistance of the primary nylon product.

[0032] S2, providing 70 to 80 parts of the nylon primary product, adding 10 to 15 parts of modified wood cellulose and 8 to 12 parts of nano-boron nitride loaded with graphene quantum dots to the nylon primary product, preheating at 70° C. for 1 hour, and mixing in a high-speed mixer at a speed of 1500 to 2000 r / min to obtain a mixed material.

[0033] Wherein, the preparation of the modified lignocellulose comprises the following steps:

[0034] The lignocellulose and the modifier solution are mixed in a mass ratio of 3:1 to 4:1, and stirred at 70 to 80°C for 2 to 4 hours to obtain modified lignocellulose. The modifier solution includes tributyl citrate and one of tetrabutyl titanate and silane coupling agent KH-550.

[0035] Specifically, by modifying lignocellulose, the dispersibility of lignocellulose in nylon is improved, and its composite effect with nylon is enhanced. The active groups on the surface of the modified lignocellulose and the amide groups in the primary nylon product form cross-links through hydrogen bonds and partial covalent bonds. The long-chain structure of lignocellulose can play a role in strengthening and toughening the nylon matrix.

[0036] In some embodiments, the modifier solution includes tributyl citrate and silane coupling agent KH-550, the volume ratio of tributyl citrate to silane coupling agent KH-550 is 3:2, and the concentration of triethyl citrate is 50wt%. The alkoxy group of KH-550 can react with the hydroxyl group on the surface of lignocellulose to improve the interfacial bonding force between lignocellulose and nylon.

[0037] In some embodiments, the modifier solution includes triethyl citrate and tetrabutyl titanate, the mass ratio of triethyl citrate to tetrabutyl titanate is 2:1, and the concentration of triethyl citrate is 50wt%; the ester group in triethyl citrate can react with the hydroxyl group on the surface of lignocellulose, and tetrabutyl titanate can promote the reaction and improve the compatibility of the modified lignocellulose with nylon, so as to improve the dispersibility of lignocellulose in nylon, enhance the strength and toughness of nylon material, and at the same time, due to the tighter bonding with nylon, it helps to improve heat resistance.

[0038] In some embodiments, the preparation of nano boron nitride loaded with graphene quantum dots comprises the following steps:

[0039] Nano boron nitride and graphene quantum dots were mixed in a mass ratio of 10:3, added into deionized water in a mass ratio of 1:4, and ultrasonically treated at 40-50° C. for 3-4 hours to obtain nano boron nitride loaded with graphene quantum dots.

[0040] Nano-boron nitride has a high specific surface area and active sites, and can form physical adsorption and chemical bonds with nylon molecules. At the same time, its high thermal conductivity can disperse heat more quickly, reduce local overheating, and improve the thermal stability of nylon materials. Graphene quantum dots have excellent thermal conductivity and mechanical properties. Loading them on nano-boron nitride can further improve the performance of nano-boron nitride. The flaky structure of nano-boron nitride can hinder the transfer of heat and improve the heat resistance of nylon.

[0041] In some embodiments, the step further includes the following steps:

[0042] Add 8-12 parts of chitosan grafted polylactic acid modified with nano-hydroxyapatite:

[0043] Chitosan grafted polylactic acid and nano-hydroxyapatite are mixed in a mass ratio of 5:2, and then added into an acetic acid solution in a mass ratio of 1:3, and reacted with stirring at 60-70°C for 3-4h to obtain nano-hydroxyapatite modified chitosan grafted polylactic acid.

[0044] In some embodiments, the preparation of chitosan grafted polylactic acid comprises the following steps:

[0045] Chitosan and 2 wt % acetic acid solution were mixed in a mass ratio of 1:10, and stirred at 25° C. until the chitosan was completely dissolved to obtain a chitosan solution;

[0046] Polylactic acid and dichloromethane are mixed in a ratio of 1:5, and stirred at 40°C until the polylactic acid is completely dissolved to obtain a polylactic acid solution, and the polylactic acid solution is added dropwise to the chitosan solution, and ammonium persulfate accounting for 2% of the total mass of the chitosan solution and the polylactic acid solution is added, and stirred at 50°C for 5 hours to obtain a chitosan grafted polylactic acid crude product solution;

[0047] The crude chitosan grafted polylactic acid product solution was allowed to stand for 2 hours and then filtered to obtain a solid, which was washed and dried to obtain chitosan grafted polylactic acid.

[0048] The chitosan part of chitosan grafted polylactic acid contains a large number of active groups such as hydroxyl and amino groups, which can form hydrogen bonds and covalent cross-links with nylon molecules. The polylactic acid part has a certain compatibility with nylon, which can improve the mechanical properties and heat resistance of the material.

[0049] The chitosan part in the chitosan-grafted polylactic acid can form hydrogen bonds and other interactions with the groups on the surface of the modified cellulose, and can also interact with nano-boron nitride through physical adsorption and other means to enhance the cross-linking between the materials.

[0050] Furthermore, chitosan is a natural degradable material, and polylactic acid is also a degradable polymer. The copolymer formed by the two can improve the environmental friendliness of the entire material in nylon materials. When the nylon material is discarded, the chitosan-grafted polylactic acid copolymer can be more easily degraded in the natural environment, reducing pollution to the environment.

[0051] S3. Add the mixture into a twin-screw extruder, add zinc phytate, an antioxidant and a compatibilizer at the same time, perform extrusion granulation, and during the extrusion process, add 30wt% triethanolamine solution according to 1.5% of the total mass of the mixture to obtain an environmentally friendly modified nylon material, wherein the zinc phytate accounts for 5-10% of the mass of the mixture, the antioxidant accounts for 2-5% of the mixture, and the compatibilizer accounts for 3-8% of the mixture, the antioxidant is selected from one of natural vitamin C and tea polyphenols, and the compatibilizer is selected from tributyl citrate grafted polyethylene.

[0052] Specifically, triethanolamine can promote the cross-linking between nylon molecules and improve the overall performance of nylon materials. On the other hand, it can react with modified wood cellulose and loaded modified nano-boron nitride active groups to form a more stable cross-linking structure.

[0053] Furthermore, zinc phytate can form a dense carbon layer at high temperature, which plays a role in heat insulation and oxygen isolation, preventing the spread of flames. At the same time, zinc phytate is a naturally derived compound and is environmentally friendly. It can form hydrogen bonds and other interactions with the amide groups in nylon molecules, enhancing the binding force with nylon, thereby improving the flame retardant properties while promoting the cross-linking of the overall material.

[0054] In some embodiments, the lignocellulose raw material is straw, and the lignocellulose is sieved through a 320-500 mesh sieve.

[0055] It should be noted that the parts in the following embodiments and comparative examples refer to parts by mass.

[0056] Example 1

[0057] S101, adding 50 parts of oxalic acid and 50 parts of 1,6-hexanediamine into a reaction kettle, heating to 180°C, stirring evenly, adding 0.5 parts of tetrabutyl titanate, heating to 250°C under nitrogen protection, reacting for 3 hours, and obtaining a primary nylon product;

[0058] S102, adding 10 parts of modified wood cellulose and 8 parts of nano-boron nitride loaded with graphene quantum dots to 70 parts of the primary nylon product, preheating at 70° C. for 1 hour, and mixing in a high-speed mixer at a speed of 1500 r / min to obtain a mixed material.

[0059] Wherein, the preparation of the modified lignocellulose comprises the following steps:

[0060] 30 parts of lignocellulose, 6 parts of 50 wt% tributyl citrate, and 4 parts of silane coupling agent KH-550 were mixed, and stirred at 70° C. for 2 hours to obtain modified lignocellulose.

[0061] The preparation of the nano boron nitride loaded with graphene quantum dots comprises the following steps:

[0062] 10 parts of nano-boron nitride and 3 parts of graphene quantum dots were mixed, added into 52 parts of deionized water, and ultrasonically treated at 40° C. for 3 h to obtain nano-boron nitride loaded with graphene quantum dots.

[0063] S103, adding the mixed material into a twin-screw extruder, and simultaneously adding 4.4 parts of zinc phytate, 1.76 parts of natural vitamin C, and 2.64 parts of tributyl citrate grafted polyethylene, for extrusion granulation, and during the extrusion process, adding 1.32 parts of a 30wt% triethanolamine solution to obtain an environmentally friendly modified nylon material.

[0064] Example 2

[0065] S201, adding 50 parts of oxalic acid and 50 parts of 1,6-hexanediamine into a reaction kettle, heating to 200°C, stirring evenly, adding 1.5 parts of tetrabutyl titanate, heating to 250°C under nitrogen protection, reacting for 4 hours, and obtaining a primary nylon product;

[0066] S202, adding 15 parts of modified wood cellulose and 12 parts of nano-boron nitride loaded with graphene quantum dots to 80 parts of the primary nylon product, preheating at 70° C. for 1 hour, and mixing in a high-speed mixer at a speed of 2000 r / min to obtain a mixed material.

[0067] Wherein, the preparation of the modified lignocellulose comprises the following steps:

[0068] 40 parts of lignocellulose, 6 parts of 50 wt% tributyl citrate, and 4 parts of silane coupling agent KH-550 were mixed, and stirred at 80° C. for 4 hours to obtain modified lignocellulose.

[0069] The preparation of the nano boron nitride loaded with graphene quantum dots comprises the following steps:

[0070] 10 parts of nano-boron nitride and 3 parts of graphene quantum dots were mixed, added into 52 parts of deionized water, and ultrasonically treated at 50° C. for 4 hours to obtain nano-boron nitride loaded with graphene quantum dots.

[0071] S203, adding the mixed material into a twin-screw extruder, and simultaneously adding 10.7 parts of zinc phytate, 5.35 parts of natural vitamin C, and 8.56 parts of tributyl citrate grafted polyethylene, for extrusion granulation, and during the extrusion process, adding 1.6 parts of a 30wt% triethanolamine solution to obtain an environmentally friendly modified nylon material.

[0072] Example 3

[0073] S301, adding 50 parts of oxalic acid and 50 parts of 1,6-hexanediamine into a reaction kettle, heating to 190°C, stirring evenly, adding 1 part of tetrabutyl titanate, heating to 250°C under nitrogen protection, reacting for 3 hours, and obtaining a primary nylon product;

[0074] S302, add 12 parts of modified wood cellulose, 10 parts of nano-boron nitride loaded with graphene quantum dots, and 10 parts of chitosan grafted polylactic acid modified with nano-hydroxyapatite to 80 parts of the primary nylon product, preheat at 70°C for 1 hour, and mix them evenly in a high-speed mixer at a speed of 1800 r / min to obtain a mixed material.

[0075] Wherein, the preparation of the modified lignocellulose comprises the following steps:

[0076] 40 parts of lignocellulose were mixed with 8 parts of 50 wt% tributyl citrate and 4 parts of tetrabutyl titanate, and stirred at 75° C. for 3 hours to obtain modified lignocellulose.

[0077] The preparation of the nano boron nitride loaded with graphene quantum dots comprises the following steps:

[0078] 10 parts of nano-boron nitride and 3 parts of graphene quantum dots were mixed, added into 52 parts of deionized water, and ultrasonically treated at 40° C. for 4 hours to obtain nano-boron nitride loaded with graphene quantum dots.

[0079] The preparation of the chitosan grafted polylactic acid modified by nano-hydroxyapatite comprises the following steps:

[0080] a. Preparation of chitosan grafted polylactic acid:

[0081] At 25° C., 8 parts of chitosan were stirred and dissolved in 80 parts of 2 wt % acetic acid solution to obtain a chitosan solution;

[0082] At 40°C, 2 parts of polylactic acid were stirred and dissolved in 10 parts of dichloromethane to obtain a polylactic acid solution, the polylactic acid solution was added dropwise to the chitosan solution, and 2 parts of ammonium persulfate were added, and the mixture was stirred and reacted at 50°C for 5 hours to obtain a chitosan grafted polylactic acid crude product solution;

[0083] The crude chitosan grafted polylactic acid product solution was allowed to stand for 2 hours and then filtered to obtain a solid, which was washed and dried to obtain chitosan grafted polylactic acid.

[0084] b. Modification of chitosan grafted with polylactic acid:

[0085] 50 parts of chitosan grafted polylactic acid and 20 parts of nano-hydroxyapatite were mixed, added into 210 parts of acetic acid solution, and reacted with stirring at 65° C. for 3 hours to obtain chitosan grafted polylactic acid modified with nano-hydroxyapatite.

[0086] S303, adding the mixed material into a twin-screw extruder, and simultaneously adding 6.72 parts of zinc phytate, 4.48 parts of natural vitamin C, and 5.6 parts of tributyl citrate grafted polyethylene, for extrusion granulation, and during the extrusion process, adding 1.68 parts of a 30wt% triethanolamine solution to obtain an environmentally friendly modified nylon material.

[0087] Example 4

[0088] S401, adding 50 parts of oxalic acid and 50 parts of 1,6-hexanediamine into a reaction kettle, heating to 190°C, stirring evenly, adding 1 part of tetrabutyl titanate, heating to 250°C under nitrogen protection, reacting for 3 hours, and obtaining a primary nylon product;

[0089] S402, adding 12 parts of modified wood cellulose, 10 parts of nano-boron nitride loaded with graphene quantum dots, and 8 parts of chitosan grafted polylactic acid modified with nano-hydroxyapatite to 75 parts of the primary nylon product, preheating at 70°C for 1 hour, and mixing in a high-speed mixer at a speed of 1800 r / min to obtain a mixed material.

[0090] Wherein, the preparation of the modified lignocellulose comprises the following steps:

[0091] 36 parts of lignocellulose, 6 parts of 50 wt% tributyl citrate and 3 parts of tetrabutyl titanate were mixed, and stirred at 75° C. for 4 hours to obtain modified lignocellulose.

[0092] The preparation of the nano boron nitride loaded with graphene quantum dots comprises the following steps:

[0093] 10 parts of nano-boron nitride and 3 parts of graphene quantum dots were mixed, added into 52 parts of deionized water, and ultrasonically treated at 45° C. for 3 h to obtain nano-boron nitride loaded with graphene quantum dots.

[0094] The preparation of the chitosan grafted polylactic acid modified by nano-hydroxyapatite comprises the following steps:

[0095] a. Preparation of chitosan grafted polylactic acid:

[0096] At 25° C., 8 parts of chitosan were stirred and dissolved in 80 parts of 2 wt % acetic acid solution to obtain a chitosan solution;

[0097] At 40°C, 2 parts of polylactic acid were stirred and dissolved in 10 parts of dichloromethane to obtain a polylactic acid solution, the polylactic acid solution was added dropwise to the chitosan solution, and 2 parts of ammonium persulfate were added, and the mixture was stirred and reacted at 50°C for 5 hours to obtain a chitosan grafted polylactic acid crude product solution;

[0098] The crude chitosan grafted polylactic acid product solution was allowed to stand for 2 hours and then filtered to obtain a solid, which was washed and dried to obtain chitosan grafted polylactic acid.

[0099] b. Modification of chitosan grafted with polylactic acid:

[0100] 50 parts of chitosan grafted polylactic acid and 20 parts of nano-hydroxyapatite were mixed, added into 210 parts of acetic acid solution, and reacted with stirring at 60° C. for 4 hours to obtain chitosan grafted polylactic acid modified with nano-hydroxyapatite.

[0101] S403, adding the mixed material into a twin-screw extruder, and simultaneously adding 6.3 parts of zinc phytate, 5.25 parts of natural vitamin C, and 6.3 parts of tributyl citrate grafted polyethylene, for extrusion granulation, and during the extrusion process, adding 1.58 parts of a 30wt% triethanolamine solution to obtain an environmentally friendly modified nylon material.

[0102] Example 5

[0103] S501, add 50 parts of oxalic acid and 50 parts of 1,6-hexanediamine into a reaction kettle, heat to 190°C, stir evenly, add 1 part of tetrabutyl titanate, heat to 250°C under nitrogen protection, react for 3.5 hours, and obtain a primary nylon product;

[0104] S502, add 12 parts of modified wood cellulose, 10 parts of nano-boron nitride loaded with graphene quantum dots, and 10 parts of chitosan grafted polylactic acid modified with nano-hydroxyapatite to 80 parts of the primary nylon product, preheat at 70°C for 1 hour, and mix them evenly in a high-speed mixer at a speed of 1800 r / min to obtain a mixed material.

[0105] Wherein, the preparation of the modified lignocellulose comprises the following steps:

[0106] 40 parts of lignocellulose were mixed with 8 parts of 50 wt% tributyl citrate and 4 parts of tetrabutyl titanate, and stirred at 75° C. for 3 hours to obtain modified lignocellulose.

[0107] The preparation of the nano boron nitride loaded with graphene quantum dots comprises the following steps:

[0108] 10 parts of nano-boron nitride and 3 parts of graphene quantum dots were mixed, added into 52 parts of deionized water, and ultrasonically treated at 40° C. for 4 hours to obtain nano-boron nitride loaded with graphene quantum dots.

[0109] The preparation of the chitosan grafted polylactic acid modified by nano-hydroxyapatite comprises the following steps:

[0110] a. Preparation of chitosan grafted polylactic acid:

[0111] At 25° C., 8 parts of chitosan were stirred and dissolved in 80 parts of 2 wt % acetic acid solution to obtain a chitosan solution;

[0112] At 40°C, 2 parts of polylactic acid were stirred and dissolved in 10 parts of dichloromethane to obtain a polylactic acid solution, the polylactic acid solution was added dropwise to the chitosan solution, and 2 parts of ammonium persulfate were added, and the mixture was stirred and reacted at 50°C for 5 hours to obtain a chitosan grafted polylactic acid crude product solution;

[0113] The crude chitosan grafted polylactic acid product solution was allowed to stand for 2 hours and then filtered to obtain a solid, which was washed and dried to obtain chitosan grafted polylactic acid.

[0114] b. Modification of chitosan grafted with polylactic acid:

[0115] 50 parts of chitosan grafted polylactic acid and 20 parts of nano-hydroxyapatite were mixed, added into 210 parts of acetic acid solution, and reacted with stirring at 70° C. for 3 hours to obtain chitosan grafted polylactic acid modified with nano-hydroxyapatite.

[0116] S503, adding the mixed material into a twin-screw extruder, and simultaneously adding 6.72 parts of zinc phytate, 4.48 parts of natural vitamin C, and 5.6 parts of tributyl citrate grafted polyethylene, for extrusion granulation, and during the extrusion process, adding 1.68 parts of a 30wt% triethanolamine solution to obtain an environmentally friendly modified nylon material.

[0117] Comparative Example 1

[0118] Except that modified lignocellulose is not added in S302, other manufacturing steps are consistent with Example 3.

[0119] Comparative Example 2

[0120] Except that nano-boron nitride loaded with graphene quantum dots is not added in S302, other manufacturing steps are consistent with those in Example 3.

[0121] Comparative Example 3

[0122] Except that modified lignocellulose and nano-boron nitride loaded with graphene quantum dots are not added in S302, other manufacturing steps are consistent with those in Example 3.

[0123] Comparative Example 4

[0124] Except that in S302 , the modified lignocellulose is replaced with lignocellulose without adding a modifier, the other manufacturing steps are the same as those of Example 3.

[0125] Comparative Example 5

[0126] Except that in S302, the nano-boron nitride carrying graphene quantum dots is replaced with nano-boron nitride, the other manufacturing steps are consistent with those of Example 3.

[0127] The mechanical properties of the environmentally friendly modified nylon materials manufactured in Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Table 1.

[0128] Table 1

[0129]

[0130] It should be noted that the heat deformation temperature in Table 1 refers to the deformation temperature of the prepared nylon material under 1.8 MPa.

[0131] For the water absorption rate, the water absorption rate was tested by immersion method. 10g of the environmentally friendly modified nylon materials obtained in Examples 1 to 5 and Comparative Examples 1 to 5 were respectively immersed in 80°C water for 1 hour. After the immersion, the surface moisture was taken out and wiped dry, and the water absorption rate was calculated by weighing. The water absorption rate calculation formula is: water absorption rate = (mass after immersion - mass before immersion) / mass before immersion × 100%.

[0132] It can be seen that the environmentally friendly modified nylon material manufactured by using Examples 3 to 5 has better tensile strength, flexural strength, higher heat deformation temperature, Vicat softening temperature, and lower water absorption.

[0133] The present application also provides an environmentally friendly modified nylon material, which is manufactured by the preparation methods provided in the above-mentioned embodiments.

[0134] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an environmentally friendly modified nylon material, characterized in that: It includes the following steps: S1. Add equal amounts of oxalic acid and 1,6-hexanediamine into a reaction kettle, heat to 180-200° C., stir evenly, add tetrabutyl titanate, heat to 250° C. under nitrogen protection, react for 3-4 hours, and obtain a primary nylon product, wherein the amount of tetrabutyl titanate added is 0.5-1.5% of the total mass of oxalic acid and 1,6-hexanediamine; S2, providing 70 to 80 parts of the nylon primary product, adding 10 to 15 parts of modified wood cellulose and 8 to 12 parts of nano-boron nitride loaded with graphene quantum dots to the nylon primary product, preheating at 70° C. for 1 hour, and mixing in a high-speed mixer at a speed of 1500 to 2000 r / min to obtain a mixed material; The preparation of the modified lignocellulose comprises the following steps: The lignocellulose and the modifier solution are mixed in a mass ratio of 3:1 to 4:1, and stirred at 70 to 80° C. for 2 to 4 hours to obtain modified lignocellulose, wherein the modifier solution includes tributyl citrate and one of tetrabutyl titanate and silane coupling agent KH-550; S3. Add the mixture into a twin-screw extruder, add zinc phytate, an antioxidant and a compatibilizer at the same time, perform extrusion granulation, and during the extrusion process, add 30wt% triethanolamine solution according to 1.5% of the total mass of the mixture to obtain an environmentally friendly modified nylon material, wherein the zinc phytate accounts for 5-10% of the mass of the mixture, the antioxidant accounts for 2-5% of the mixture, and the compatibilizer accounts for 3-8% of the mixture, the antioxidant is selected from one of natural vitamin C and tea polyphenols, and the compatibilizer is selected from tributyl citrate grafted polyethylene.

2. The method for preparing the environmentally friendly modified nylon material according to claim 1, characterized in that: The preparation of the nano boron nitride loaded with graphene quantum dots comprises the following steps: Nano boron nitride and graphene quantum dots were mixed in a mass ratio of 10:3, added into deionized water in a mass ratio of 1:4, and ultrasonically treated at 40-50° C. for 3-4 hours to obtain nano boron nitride loaded with graphene quantum dots.

3. The method for preparing the environmentally friendly modified nylon material according to claim 1, characterized in that: The S2 further includes: Add 8-12 parts of chitosan grafted polylactic acid modified with nano-hydroxyapatite: Chitosan grafted polylactic acid and nano-hydroxyapatite are mixed in a mass ratio of 5:2, and then added into an acetic acid solution in a mass ratio of 1:3, and reacted with stirring at 60-70°C for 3-4h to obtain nano-hydroxyapatite modified chitosan grafted polylactic acid.

4. The method for preparing the environmentally friendly modified nylon material according to claim 3, characterized in that: The preparation of chitosan grafted polylactic acid comprises the following steps: Chitosan and 2 wt % acetic acid solution were mixed in a mass ratio of 1:10, and stirred at 25° C. until the chitosan was completely dissolved to obtain a chitosan solution; Polylactic acid and dichloromethane are mixed in a ratio of 1:5, and stirred at 40°C until the polylactic acid is completely dissolved to obtain a polylactic acid solution, and the polylactic acid solution is added dropwise to the chitosan solution, and ammonium persulfate accounting for 2% of the total mass of the chitosan solution and the polylactic acid solution is added, and stirred at 50°C for 5 hours to obtain a chitosan grafted polylactic acid crude product solution; The crude chitosan grafted polylactic acid product solution was allowed to stand for 2 hours and then filtered to obtain a solid, which was washed and dried to obtain chitosan grafted polylactic acid.

5. The method for preparing the environmentally friendly modified nylon material according to claim 1, characterized in that: The modifier solution includes tributyl citrate and silane coupling agent KH-550, the volume ratio of the tributyl citrate to the silane coupling agent KH-550 is 3:2, and the concentration of the triethyl citrate is 50wt%.

6. The method for preparing the environmentally friendly modified nylon material according to claim 1, characterized in that: The modifier solution includes triethyl citrate and tetrabutyl titanate, the mass ratio of the triethyl citrate to the tetrabutyl titanate is 2:1, and the concentration of the triethyl citrate is 50wt%.

7. An environmentally friendly modified nylon material, which is produced by the method for preparing an environmentally friendly modified nylon material as claimed in any one of claims 1 to 6.